What are the Mechanisms and Contexts for a Supported Life After Stroke Pathway: Protocol for a Rapid Realist Review [version 3; peer review: 2 approved, 1 approved with reservations] - Killian Walsh; Frances Horgan; Olive Lennon; Mary O'Neill (HRB Open Research, 2025)
Background Ever-growing numbers of individuals are surviving stroke and living with the consequences. Life after stroke is a key pillar in addressing the burden of stroke for the remaining lifespan for those with stroke. No consensus on how to best promote agency and fulfilment in life after stroke or the resources required to achieve this currently exists. Methods In this realist review protocol we outline the methods we will use to gain an understanding of supporting Life after Stroke through the development of programme theories. These will consist of context–mechanism–outcome configurations (CMOCs) and will acknowledge the resources required. The review will follow the RAMESES five-stage structured methodology to (1) define the scope of the review, and the development of initial programme theories for supporting life after stroke, (2) develop a comprehensive search strategy to identify relevant research, (3) review primary studies and extract data, (4) synthesise evidence (5) refine programme theories iteratively throughout the process using an Expert Panel and reference group, to including stroke researchers, health care professionals working in stroke care, people with lived experience of stroke and carers, and stroke support agencies. Conclusion This realist review will examine the mechanisms and contexts for a supported life after stroke care pathway. The CMOCs developed will help explain how generative causation within the life after stroke pathway works. The findings will help inform policy and practice and inform future realist evaluations of Life after Stroke support pathways.